Association between Teaching and Learning Related Stressor and Anxiety Level among Medical Students during COVID-19 Pandemic - Melia Fatrani Rufaidah; Helda Helda; Sarah At Tauhidah (Journal of Health Promotion and Behavior, 2021)
Background: The COVID-19 pandemic has led to various impacts on public health, one of which is the mental health of medical students who are recognized as an at-risk group for developing anxiety disorders due to the teaching and learning system that has changed dramatically. This study aimed to assess the relationship between teaching and learning-related stressor (TLRS) and their anxiety levels during the COVID-19 pandemic.Subjects and Method: This was a cross-sectional study. The population was medical students at the Faculty of Medicine, Syarif Hidayatullah State Islamic University Jakarta, Indonesia, during September-October 2021. Sampling was carried out using purposive sampling. The dependent variable was anxiety levels during the COVID-19 pandemic. The independent variable was teaching and learning-related stressor based on Medical Student Stressor Questionnaire (MSSQ) instrument. The data were collected through questionnaires and analyzed by Cox proportional regression.Results: A half of medical students experienced anxiety (50.4%), but the data shows a non-significant difference when controlled with other stressor variables (Adjusted PR= 1.485; 95% CI= 0.71 to 2.97; p= 0.300).Conclusion: There is no significant relationship between teaching and learning-related stressor and anxiety level among Medical Students during COVID-19 pandemic.Keywords: mental health, anxiety, stressor, COVID-19, medical studentsCorrespondence:Helda. Department of Epidemiology, Faculty of Public Health Universitas Indonesia. A Building 1st Floor Kampus Baru UI Depok 16424. E-mail: heldanazar1@gmail.com. Phone: +6285216688437Journal of Health Promotion and Behavior (2021), 06(04): 263-271DOI: https://doi.org/10.26911/thejhpb.2021.06.04.01